DESCRIPTION OF THE SCHOOLS AND SCHOOLS OF THE BUKH Emirate IN THE "MEMORIES" OF SADRIDDIN AYNI (Scientific journal of the Fergana State University, 2024)
The article analyzes information about the activities of old-style schools and madrasas contained in the “Memoirs” of the outstanding writer and scientist Sadriddin Aini. Taking into account the fact that the author himself studied in an old-style school and madrasah for many years, the reliability of the provided information and the importance of his memoirs as a source on the history of the education system in the Bukhara Emirate are emphasized.